Instagram sebagai Media Informasi Digital Kota Bogor : Studi pada Konten Reels @Bogordailynews - M Meyzal Kesyahda; Wahyu Budi Priatna (Lembaga Pengembangan Kinerja Dosen, 2026)
The development of digital information media has changed the way people obtain information, especially in urban areas that require fast and up-to-date information. Instagram is now used not only for entertainment and social interaction but also as a digital information medium. One local media account that actively presents information about Bogor City through the Reels feature is @bogordailynews. This study aims to analyze the characteristics and types of information presented by @bogordailynews with the Reels feature and analyze the media functions reflected in the content. The study used a qualitative approach with a content analysis method. The research data consisted of Reels content uploaded by the @bogordailynews account over a certain period and collected through observation, documentation, and literature studies. The findings of this study indicate that Reels content is dominated by information about traffic conditions, social events, public policies, and community activities in Bogor City. Information is presented concisely, visually, quickly, and up-to-date, in accordance with the characteristics of digital media. Reels content demonstrates the media's function as an information provider, event explainer, and conveyor of social values. This study indicates that Instagram plays an important role as an information medium for urban communities.